Geosynthetic materials in transportation engineering - Mersin, Denizhan (My University, 2022)
As in all areas of technology, an increase is observed in the production and use of innovative materials in engineering applications. Geosynthetics are materials produced from polymeric materials and are widely used in civil engineering, and the main ones can be listed as geonet, geomembrane, geotextile, geogrid, geocomposite, geofoam, and geocell. Conservation of resources and energy in the realized applications and existing projects necessitates the preference for quality geosynthetic materials and qualified geosynthetic applications to ensure sustainability. Transportation engineering, which is a branch of civil engineering, covers roads (pavements), airports, ports, and railways. Besides, geosynthetic materials increase the performance and design life of transportation structures, especially in areas where soil strength is weak. Geosynthetics offer much higher value than traditional road construction products and greatly reduce construction with a fast, simple installation process. This study reviews the various functions and benefits of several geosynthetic material types in transportation structures.
Bildiri - Yayımlanmış
Keywords: Environment; Geotechnics; Geosynthetics; Civil engineering; Transportation engineering